Pengaruh Komitmen Manajemen, Aksesibilitas Laporan Keuangan, Penyajian Laporan Keuangan, dan Pengendalian Internal Terhadap Penerapan Transparansi Pelaporan Keuangan Pada SKPD di Kota Denpasar - Ni Kadek Putri Purnamadewi; Ni Putu Riasning; I Wayan Rupa (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Warmadewa, 2021)
This study aims to find the effect of management commitment, accessibility of financial reports, presentation of financial statements, and internal control on the implementation of financial reporting transparency. The location of this research is SKPD Denpasar City. The population in this study was the SKPD of Denpasar City, amounting to 21 SKPD, each SKPD was taken by four officials who were involved in the preparation of financial statements so that the sample of this study was 84 respondents. The analysis technique used in this research is multiple linear regression analysis. The results of this study indicate that management commitment has a positive and significant effect on financial reporting transparency, financial report accessibility has a positive and significant effect on financial reporting transparency, financial reporting has a positive and significant effect on financial reporting transparency, internal control has a positive and significant effect on financial reporting transparency.